(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the problem of the conflict in Ukraine, as well as its impact on the countries of Central Asia. Ukrainian crisis is most acute and urgent in modern international processes. Differences West and Russia, to impose sanctions on Russia, the proliferation of new conflicts – all of this is a consequence of the conflict in Ukraine, which began in February 2014. The study is carried out in detail the possibility of repetition of the Ukrainian scenario in Central Asia. The fully set forth the position of the Republic of Kazakhstan and the Central Asian countries in respect of this problem. On the basis of the study authors have systematically analyzed the current situation and make further forecast the impact of events in Ukraine for the domestic and foreign policies of Central Asian countries. Key words: Republic of Kazakhstan, Ukraine, Central Asia, Kyrgyzstan, Uzbekistan, Tajikistan, Turkmenistan, foreign policy, Ukrainian conflict.